2014
DOI: 10.1111/micc.12116
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training‐Induced Adaptations in Mediators of Sustained Endothelium‐Dependent Coronary Artery Relaxation in a Porcine Model of Ischemic Heart Disease

Abstract: Objective Test the hypothesis that exercise training enhances sustained relaxation to persistent endothelium-dependent vasodilator exposure via increased nitric oxide contribution in small coronary arteries of control and ischemic hearts. Methods Yucatan swine were designated to a control group or a group in which an ameroid constrictor was placed around the proximal LCX. Subsequently, pigs from both groups were assigned to exercise (5 days/week; 16 weeks) or sedentary regimens. Coronary arteries (~100–350 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
(75 reference statements)
3
6
0
1
Order By: Relevance
“…These data are consistent with our more recent findings that endothelial nitric oxide synthase protein is significantly increased in collateral-dependent compared with nonoccluded arteries of exercise-trained pigs [23]. We have also reported enhanced bradykinin-mediated relaxation in collateral-dependent arteries of exercise-trained pigs that is reversed by NOS inhibition [23]. Furthermore, others have reported that nitric oxide synthase inhibition decreases blood flow into the collateral-dependent region more so during exercise than at rest [53], providing evidence that the contribution of nitric oxide increases as coronary metabolic demand rises in the compromised myocardial region.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These data are consistent with our more recent findings that endothelial nitric oxide synthase protein is significantly increased in collateral-dependent compared with nonoccluded arteries of exercise-trained pigs [23]. We have also reported enhanced bradykinin-mediated relaxation in collateral-dependent arteries of exercise-trained pigs that is reversed by NOS inhibition [23]. Furthermore, others have reported that nitric oxide synthase inhibition decreases blood flow into the collateral-dependent region more so during exercise than at rest [53], providing evidence that the contribution of nitric oxide increases as coronary metabolic demand rises in the compromised myocardial region.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we have previously reported that NOS inhibition results in a significant increase in sensitivity (EC 50 ) to ET-1 in collateral-dependent but not nonoccluded arteries of exercisetrained pigs [46]. These data are consistent with our more recent findings that endothelial nitric oxide synthase protein is significantly increased in collateral-dependent compared with nonoccluded arteries of exercise-trained pigs [23]. We have also reported enhanced bradykinin-mediated relaxation in collateral-dependent arteries of exercise-trained pigs that is reversed by NOS inhibition [23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Intracellular Ca 2+ levels were measured using fura-2AM in phenol-free DMEM media as described [65][66][67] . LMCs were plated in glass bottom chamber and treated when LMCs reached 60% confluence.…”
Section: Intracellular Ca 2+ Measurement In Lmcsmentioning
confidence: 99%